Pengaruh Profitabilitas, Sales Growth, dan Leverage terhadap Financial Distress dengan Pendekatan Springate S-score - Yuntini, Kadek; Wahyuni, Made Arie; Vijaya, Diota Prameswari (Forum Kerjasama Pendidikan Tinggi, 2026)
This study is motivated by the decline in financial performance accompanied by the disclosure of fraud cases at PT Kimia Farma Tbk and PT Indofarma Tbk, as well as indications of deteriorating financial conditions among pharmaceutical sub-sector companies during the 2021–2024 period. These conditions highlight the importance of early detection of financial distress to prevent more severe financial problems. This study aims to empirically examine the effect of profitability, sales growth, and leverage on financial distress measured using the Springate s-score model in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. This research employs a quantitative approach using multiple linear regression analysis and purposive sampling technique, resulting in 40 firm-year observations during the research period. The F-test results indicate that profitability, sales growth, and leverage simultaneously affect financial distress (F = 114.129; p < 0.001), indicating strong model feasibility. Partially, profitability has a significant positive effect on the S-Score (coefficient = 2.530; p < 0.001), indicating that higher profitability reflects healthier financial conditions. Leverage also has a significant negative effect on the S-Score (coefficient = ?1.720; p < 0.001), implying that higher leverage increases the risk of financial distress. Meanwhile, sales growth does not have a significant effect on financial distress (coefficient = ?0.226; p = 0.241). The findings of this study are expected to contribute to early detection of financial distress risk and serve as a consideration for management and investors in decision-making and strengthening corporate governance.